The generalized solutions of a certain n order differential equations with polynomial coefficients - K. Nonlaopon (2018)
© 2015 Taylor & Francis. In this paper, we propose the generalized solutions of the differential equation (Formula presented.) where m and n are any integers with (Formula presented.) , and (Formula presented.) using Laplace transform technique. We find that the types of Laplace transformable solutions in the space of right-sided distributions depend on the relationship between m and n. Precisely, we have a distributional solution provided (Formula presented.) , and a weak solution otherwise. Our work improves the result of Kananthai [The distribution solutions of ordinary differential equation with polynomial coefficients. Southeast Asian Bull Math. 2001;25:129–134].